79.7k views
4 votes
Given the matrices A =

2
2
3
4
B=
0
4
2
-3
C=
4
6
5
6
the matrix X in the equation (x-4b)a=c

1 Answer

4 votes

Answer:

Hello,

Explanation:


A=\begin{bmatrix}2 & 2 \\3 & 4 \end{bmatrix}\\\\\\B=\begin{bmatrix}0 & 4 \\2 & -3 \end{bmatrix}\\\\\\C=\begin{bmatrix}4 & 6 \\5 & 6 \end{bmatrix}\\\\\\(X-4B)*A=C\\\\X-4B=C*A^(-1)\\\\X=C*A^(-1)+4B\\


\begin{array}A&&A^(-1)&\\---&---&---&---\\2&2&1&0\\3&4&0&1\\---&---&---&---\\1&1&(1)/(2)&0\\0&1&(-3)/(2)&1\\---&---&---&---\\1&0&2&-1\\0&1&(-3)/(2)&1\\---&---&---&---\\\end {array}\\\\


X=C*A^(-1)+4B=\begin{bmatrix}4 & 6 \\5 & 6 \end{bmatrix}*\begin{bmatrix}2&-1\\(-3)/(2)&1\end{bmatrix}+4*\begin{bmatrix}0 & 4 \\2 & -3 \end{bmatrix}


X=\begin{bmatrix}-1 & 2 \\1 & 1 \end{bmatrix}+\begin{bmatrix}0 & 16 \\8 & -12 \end{bmatrix}\\\\\\X=\begin{bmatrix}-1 & 18 \\9 & -11 \end{bmatrix}\\

User Chris Lea
by
5.4k points